Cryptic marine gastropods in Hawai’i exhibit variable response to multidecadal in situ environmental changes - McClaran Shirley; Amber Dawn Stubler (PLoS ONE, 2026)
Natural history collections are a valuable tool to assess the effects of broad-scale and long-term environmental change on a diverse assemblage of species. Measurements from species that have been repeatedly collected over time within the same region provide an opportunity to infer morphological differences that have arisen as changes have occurred at the actual in situ rate of change. Using a natural history shell collection with a strong regional focus, we assessed morphological changes in marine gastropods collected from Waianae, Oahu, Hawai’i, USA from 1974–2007 to investigate the consequences of in situ changes in environmental conditions. We measured shell length and weight of 1,502 specimens representing 37 species and 19 families. Most species were cryptic, micro-shelled species (n = 25; 67.5% of species) and had a mean length of less than 5 mm. Regression and linear mixed model analyses of log-transformed weight-to-length ratio by collection year, found that the majority of species (30 out of 37) did not exhibit any temporal trend, while 7 species exhibited significant declines over time. Though the observational format of museum collection studies constrains the ability to establish causal relationships between morphometric shifts and environmental changes, these findings offer insight into the potential resiliency and vulnerability of these cryptic, non-charismatic gastropods over an ecologically relevant timescale.